Analysis of Indentation Test Using SolidWorks Simulation - Zwalnan, Selfa; Gukop, Nicholas Sylvester; Kamtu, Peter Muar (Emerging Advances in Integrated Technology, 2025)
The finite element analysis of spherical indentation was conducted using the SolidWorks simulation software. The relationship between the load and indention was determined, and comparison with the Hertzian solution was made. In this study spherical indenters of diameter 5, 10 and 15 mm were used to assess the effect of indenter radius on indentation response at a specified load. The outcome of our study shows that the resulting load-indentation response does not closely correlate; as a result, a difference of 21.2% was observed between the hertz solution and simulated results. The increase in diameter was observed to be associated with the corresponding decrease in indentation depth and the indentation stress. The von Mises stress contour at maximum load was analysed and was observed to be highest on the indented surface beneath the indenter. The resultant displacement contour shows a uniform displacement distribution